Method for preparing super absorbent
Through the hot surface post-crosslinking and cooling method of the contact dryer, the two-level axle stirring tool and two-component nozzle dosing technology are used to solve the problems of uneven coating and agglomeration of super absorbent particles, and the permeability and absorption rate of the gel bed are improved.
Patent Information
- Application Number
- CN202380090635.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-05
- Filing Date
- 2023-12-20
- Publication Date
- 2025-08-12
AI Technical Summary
The prior art is difficult to achieve uniform coating of superabsorbent particles and avoid agglomeration, which affects their application properties such as gel bed permeability and absorption.
The contact dryer is used for post-crosslinking and cooling of the hot surface. Using a stirring tool with two horizontal shafts, particulate solid substances, aqueous solutions and dispersions are added on both sides of the contact dryer to control the droplet size and throughput to ensure uniform coating and cooling.
The uniform coating of super absorbent particles is achieved, which reduces agglomeration, improves the permeability and absorption of gel beds, and improves product quality.
Smart Images

Figure BDA0005483718640000021
Abstract
Description
[0001] The invention relates to a method for producing superabsorbents, wherein superabsorbent particles are coated by spraying with a surface postcrosslinker solution, the coated superabsorbent particles are thermally surface postcrosslinked in a contact dryer 1, and the thermally surface postcrosslinked superabsorbent particles are cooled in a contact dryer 2 via two horizontal shafts, and the granular solid substance, the aqueous solution and / or the dispersion are each added via at least one first nozzle in the first horizontal axis region and at least one second nozzle in the second horizontal axis region of the contact dryer 2.
[0002] Superabsorbents are used in the manufacture of diapers, tampons, sanitary napkins, and other hygiene products, but are also used as water-retaining agents in agriculture and horticulture. Superabsorbents are also known as water-absorbing polymers.
[0003] The preparation of superabsorbents is described in the monograph "Modern Superabsorbent Polymer Technology", FL Buchholz and AT Graham, Wiley-VCH, 1998, pp. 71-103.
[0004] To improve application properties such as Gel Bed Permeability (GBP) and 2 The absorption rate under pressure (AUL0.7psi) of the superabsorbent particles is usually post-crosslinked. This increases the degree of crosslinking on the particle surface, so that the absorption rate under pressure of 49.2g / cm 2 The absorbency under pressure (AUL 0.7 psi) and the centrifuge retention capacity (CRC) can be at least partially decoupled. This surface postcrosslinking can be carried out in the aqueous gel phase. However, preferably, the surface postcrosslinker is applied to the surface of the dried, ground, and sieved polymer particles (base polymer) and then subjected to thermal postcrosslinking. Suitable crosslinkers for this purpose are compounds that can form covalent bonds with at least two carboxyl groups of the polymer particles.
[0005] It is an object of the present invention to provide an improved process for coating surface postcrosslinked superabsorbent particles, in particular for uniform coating and avoidance of agglomerations.
[0006] This object is achieved by a method for producing a superabsorbent, wherein superabsorbent particles are coated by spraying a surface postcrosslinker solution, the coated superabsorbent particles are thermally surface postcrosslinked in a contact dryer 1, and the thermally surface postcrosslinked superabsorbent particles are cooled in a contact dryer 2, characterized in that the contact dryer 2 has two horizontal shafts with stirring tools, the rotational speed of the stirring tools corresponds to a Froude number of 0.005 to 0.25, and the granular solid matter, the aqueous solution and / or the dispersion are each added to the contact dryer 2 via at least one first nozzle in the region of the first horizontal shaft and at least one second nozzle in the region of the second horizontal shaft.
[0007] In the context of the present invention, the horizontal axis located to the right of the product flow direction is the first axis, and the horizontal axis located to the left of the product flow direction is the second axis.
[0008] Examples of contact dryers suitable for the continuous process of the present invention include paddle dryers and disc dryers. In contact dryers, the material to be dried is conveyed and turned along a heated surface by a power tool. Contact dryers can also be used for cooling.
[0009] The Froude number corresponding to the rotational speed of the stirring tool is preferably 0.01 to 0.21, particularly preferably 0.02 to 0.18, and even more particularly preferably 0.05 to 0.15.
[0010] For a stirrer with horizontally supported stirring tools, the Froude number is defined as follows:
[0011]
[0012] in,
[0013] r: Radius of the stirring tool
[0014] ω: angular frequency
[0015] g: acceleration due to gravity
[0016] The granular solid matter, aqueous solution and / or dispersion can be added to the contact dryer 2 below the surface of the product bed, preferably at least 10 mm, particularly preferably at least 50 mm, very particularly preferably at least 100 mm below the surface of the product bed.
[0017] The granular solid material can be fed into the contact dryer 2 in a dispersed manner in a gas stream. The aqueous solution and / or dispersion can be fed into the contact dryer 2 via a two-component nozzle or a hydraulic nozzle.
[0018] Two-component nozzles allow atomization into fine droplets or sprays. A circular or elliptical solid or hollow cone is used for the atomization pattern. Two-component nozzles can be designed with either external or internal agitation. In externally agitated two-component nozzles, the liquid and atomizing gas exit the nozzle tip through separate openings. They are only agitated in the spray jet after leaving the nozzle. This allows independent control of droplet size distribution and throughput within a wide range. The nozzle's spray cone can be adjusted by adjusting the position of the air cap. In internally agitated two-component nozzles, the liquid and atomizing gas are agitated within the nozzle, and the two-phase mixture exits the nozzle tip through the same orifice or through several parallel orifices. In internally agitated two-component nozzles, the volume and pressure ratios are more closely coupled than in externally agitated nozzles. Therefore, even small changes in throughput result in changes in droplet size distribution. The desired throughput can be adjusted by selecting the cross-section of the nozzle orifice.
[0019] Suitable atomizing gases are compressed air, gases at 0.5 bar and above, or steam. The droplet size can be adjusted individually via the ratio of liquid to atomizing gas and the pressures of the gas and liquid.
[0020] The granular solids, aqueous solutions, and / or dispersions are fed into the contact dryer 2 below the surface of the product bed via at least two opposing nozzles. The opposing sides are determined by the position of the two horizontal axes and the conveying direction. The granular solids, aqueous solutions, and / or dispersions must be fed via at least one nozzle on the right side of the contact dryer 2 and at least one nozzle on the left side of the contact dryer 2. The contact dryer 2 can also have several pairs of such nozzles. It is advantageous if the two nozzles of a pair are approximately opposite each other.
[0021] In the contact dryer 2 , the angle between the horizontal axis and the nozzle is preferably approximately 90°. The granular solid matter, aqueous solution, and / or dispersion can be fed vertically from above. An inclined feed from below or from the side is also possible, preferably at an angle between 0° and 90°, particularly preferably between 0° and 70°, and very particularly preferably between 0° and 50° relative to the vertical. The inclined feed arrangement allows for the use of shorter feeds, thereby reducing mechanical stress during operation of the contact dryer 2 .
[0022] The present invention is based on the recognition that it is difficult to uniformly stir granular solids, aqueous solutions, and dispersions in the cooler (contact dryer 2). This is due to the insufficient stirring capacity of the contact dryer. Therefore, it is necessary to add the granular solids, aqueous solutions, or dispersions to both sides of the contact dryer 2.
[0023] The temperature of the superabsorbent particles during spraying of the surface postcrosslinker is preferably 30 to 80°C, particularly preferably 35 to 75°C, further particularly preferably 40 to 70°C.
[0024] The surface postcrosslinker solution preferably contains 0.001 to 2 wt %, particularly preferably 0.01 to 1 wt %, and more particularly preferably 0.03 to 0.7 wt %, of surface postcrosslinker, based on the superabsorbent particles. The surface postcrosslinker solution also preferably contains 0.5 to 5 wt %, particularly preferably 1.0 to 4 wt %, and more particularly preferably 1.5 to 3 wt %, of water, based on the superabsorbent particles.
[0025] In the contact dryer 1, the superabsorbent particles are heated to a temperature of preferably 110° C. to 220° C., particularly preferably 120° C. to 210° C., and more particularly preferably 130° C. to 200° C. The residence time of the superabsorbent particles in the contact dryer 1 is preferably 10 to 60 minutes, particularly preferably 15 to 50 minutes, and more particularly preferably 20 to 40 minutes.
[0026] The contact dryer 1 and the connection to the contact dryer 2 can be provided with auxiliary heating and / or thermal insulation.
[0027] The amount of particulate solid material added is preferably 0.001 to 2.0 wt %, particularly preferably 0.01 to 1.0 wt %, and even more particularly preferably 0.1 to 0.5 wt %, based on the superabsorbent particles. The average particle size of the particulate solid material is preferably 0.1 to 100 μm, particularly preferably 0.5 to 50 μm, and even more particularly preferably 1 to 25 μm. The average particle size is the volume average particle size and can be determined by light scattering. Suitable particulate solid materials are aluminum trihydroxide, silicon dioxide, and / or aluminum oxide.
[0028] During coating with the particulate solid substance, the temperature of the superabsorbent particles is preferably less than 180° C., particularly preferably less than 160° C., and even more particularly preferably less than 140° C.
[0029] The superabsorbent particles are cooled in the contact dryer 2 to a temperature of preferably 30° C. to 80° C., particularly preferably 35° C. to 70° C., and more particularly preferably 40° C. to 60° C. The residence time of the superabsorbent particles in the contact dryer 2 is preferably 10 minutes to 60 minutes, particularly preferably 15 minutes to 50 minutes, and more particularly preferably 20 minutes to 40 minutes.
[0030] The stirring tool of the contact dryer 2 preferably has a diameter of 0.2 to 2 m, particularly preferably 0.4 to 1.2 m, and more particularly preferably 0.6 to 1.2 m. The rotation speed of the stirring tool is preferably less than 25 rpm, particularly preferably less than 20 rpm, and more particularly preferably less than 15 rpm.
[0031] The preparation of superabsorbent is described in detail below.
[0032] Superabsorbents are prepared by polymerizing a monomer solution and are generally insoluble in water.
[0033] The ethylenically unsaturated monomer carrying an acid group is preferably water-soluble, i.e., its solubility in water at 23° C. is generally at least 1 g / 100 g of water, preferably at least 5 g / 100 g of water, particularly preferably at least 25 g / 100 g of water, and even more particularly preferably at least 35 g / 100 g of water.
[0034] Suitable monomers are, for example, ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, and itaconic acid. Particularly preferred monomers are acrylic acid and methacrylic acid. Acrylic acid is further particularly preferred.
[0035] Ethylenically unsaturated monomers carrying acid groups are usually partially neutralized. Neutralization is carried out at the monomer stage. This is usually achieved by mixing in a neutralizing agent in the form of an aqueous solution or preferably a solid. The degree of neutralization is preferably 40 to 85 mol %, particularly preferably 50 to 80 mol %, and even more preferably 60 to 75 mol %. Conventional neutralizing agents can be used, preferably alkali metal hydroxides, alkali metal oxides, alkali metal carbonates, or alkali metal bicarbonates, and mixtures thereof. Ammonium salts can also be used instead of alkali metal salts. Particularly preferred alkali metals are sodium and potassium, but sodium hydroxide, sodium carbonate, or sodium bicarbonate, and mixtures thereof, in particular sodium hydroxide, are particularly preferred.
[0036] The monomers generally contain a polymerization inhibitor, preferably a hydroquinone half ether which acts as a storage stabilizer.
[0037] Suitable crosslinking agents are compounds having at least two groups suitable for crosslinking. Examples of such groups include ethylenically unsaturated groups that can be free-radical polymerized into the polymer chain, and functional groups that can form covalent bonds with the acid groups of the monomers. In addition, polyvalent metal salts that can form coordinate bonds with at least two acid groups of the monomers are also suitable as crosslinking agents.
[0038] Suitable crosslinkers are, for example, ethylene glycol dimethacrylate, diethylene glycol diacrylate, polyethylene glycol diacrylate, allyl methacrylate, trimethylolpropane triacrylate, triallylamine, tetraallylammonium chloride, tetraallyloxyethane, as described in EP 0 547 847 A1, EP 0 559 476 A1, EP 0 632 068 A1, WO 93 / 21237 A1, WO 03 / 104299 A1, WO 03 / 104300 A1, WO 03 / 104301 A1 and DE 103 31450 A1, diacrylates and triacrylates as described in DE 103 31 456 A1 and DE 103 Mixed acrylates which contain ethylenically unsaturated groups in addition to acrylate groups, as described in 55401 A1, or crosslinker mixtures as described, for example, in DE 195 43 368 A1, DE 196 46 484 A1, WO 90 / 15830 A1 and WO 02 / 032962 A2.
[0039] The amount of the crosslinking agent is preferably 0.05 wt % to 1.5 wt %, particularly preferably 0.1 wt % to 1 wt %, and further particularly preferably 0.15 wt % to 0.6 wt %, based on the total amount of the monomers used. As the crosslinking agent content increases, the centrifuge retention capacity (CRC) decreases, and at 21.0 g / cm 2 The absorption rate under pressure (AUL0.3psi) passes through a maximum value.
[0040] All compounds that generate free radicals under polymerization conditions can be used as initiators, for example thermal initiators, redox initiators, photoinitiators. Suitable redox initiators are sodium peroxodisulfate / ascorbic acid, hydrogen peroxide / ascorbic acid, sodium peroxodisulfate / sodium bisulfite and hydrogen peroxide / sodium bisulfite. Preference is given to using mixtures of thermal initiators and redox initiators, such as sodium peroxodisulfate / hydrogen peroxide / ascorbic acid. Preferably, the disodium salt of 2-hydroxy-2-sulfinatoacetic acid or a mixture of the sodium salt of 2-hydroxy-2-sulfinatoacetic acid, the disodium salt of 2-hydroxy-2-sulfinatoacetic acid and sodium bisulfite is used as the reducing component. Commercially available mixtures of this type are FF6 and FF7 (Brüggemann Chemicals; Heilbronn; Germany).
[0041] The water content of the monomer solution is preferably 40 wt% to 75 wt%, particularly preferably 45 wt% to 70 wt%, and even more particularly preferably 50 wt% to 65 wt%. As the water content increases, the energy consumption in the subsequent drying process increases. When the water content decreases, the polymerization heat may not be fully dissipated.
[0042] The temperature of the monomer solution is preferably 10°C to 90°C, particularly preferably 20°C to 70°C, and further particularly preferably 30°C to 50°C.
[0043] To achieve optimal results, the preferred polymerization inhibitor requires dissolved oxygen. Therefore, prior to polymerization, the monomer solution can be purged of dissolved oxygen by inerting, i.e., by passing an inert gas, preferably nitrogen or carbon dioxide, through the monomer solution. Preferably, the oxygen content of the monomer solution is reduced to less than 1 wppm, particularly preferably to less than 0.5 wppm, and even more particularly to less than 0.1 wppm, prior to polymerization.
[0044] Suitable reactors for polymerization are, for example, kneading reactors or belt reactors. In kneaders, the polymer gel produced during the polymerization of an aqueous monomer solution or suspension is continuously comminuted, for example, by counter-rotating agitator shafts, as described in WO 2001 / 038402 A1. Polymerization in belt reactors is described, for example, in DE 38 25 366 A1 and US Pat. No. 6,241,928. Polymerization in belt reactors produces polymer gels that must be comminuted, for example, in an extruder or kneader.
[0045] To improve the drying properties, the comminuted polymer gel obtained by the kneader can additionally be extruded.
[0046] Subsequently, the polymer gel is usually dried using a belt dryer with circulating air to a moisture content of preferably 0.5 to 10 wt %, particularly preferably 1 to 7 wt %, and even more particularly preferably 2 to 5 wt %, wherein the residual moisture content is determined according to the test method No. WSP 230.2-05 "Mass Loss Upon Heating" recommended by EDANA. In the case of excessively high residual moisture, the dried polymer gel has an excessively low glass transition temperature T g, and further processing becomes difficult. If the residual moisture is too low, the dried polymer gel becomes too brittle, and an undesirably large amount of superabsorbent particles with excessively small particle sizes ("fines") is produced in the subsequent comminution step. The solids content of the polymer gel before drying is preferably 25 to 90 wt%, particularly preferably 35 to 70 wt%, and even more particularly preferably 40 to 60 wt%. The dried polymer gel is then broken up and optionally coarsely comminuted.
[0047] The dried polymer gel is then usually ground and classified, wherein grinding can usually be carried out using single-stage or multi-stage roller mills (preferably two-stage or three-stage roller mills), pin mills, hammer mills or vibration mills.
[0048] The average particle size of the superabsorbent particles separated as the product fraction is preferably at least 150 μm to 850 μm, particularly preferably 250 μm to 600 μm, and even more particularly preferably 300 μm to 500 μm. The average particle size of the product fraction can be determined using the test method No. WSP 220.2 (05) "Partikel Size Distribution" recommended by EDANA, in which the sieved mass fractions are plotted cumulatively and the average particle size is determined graphically. The average particle size is the mesh width corresponding to 50% by weight of the cumulative mass.
[0049] To further improve the properties, the superabsorbent particles are subjected to thermal surface postcrosslinking. Suitable surface postcrosslinkers are compounds containing groups capable of forming covalent bonds with at least two carboxyl groups of the superabsorbent particles. Suitable compounds are, for example, polyfunctional amines, polyfunctional aminoamines, polyfunctional epoxides, as described in EP 0 083 022 A2, EP 0 543 303 A1, and EP 0 937 736 A2, difunctional or polyfunctional alcohols, as described in DE 33 14 019 A1, DE 35 23 617 A1, and EP 0 450 922 A2, or β-hydroxyalkylamides, as described in DE 102 04 938 A1 and US Pat. No. 6,239,230.
[0050] In a preferred embodiment of the present invention, in addition to the surface postcrosslinkers, polyvalent cations are additionally applied to the particle surface.
[0051] Polyvalent cations that can be used in the method of the present invention include, for example, divalent cations such as cations of zinc, magnesium, calcium, and strontium, trivalent cations such as cations of aluminum, iron, chromium, rare earth elements, and manganese, and tetravalent cations such as cations of titanium and zirconium. Possible counterions include chlorides, bromides, hydroxides, sulfates, hydrogensulfates, carbonates, hydrogencarbonates, nitrates, phosphates, hydrogenphosphates, dihydrogenphosphates, and carboxylates such as acetates and lactates. Aluminum hydroxide, aluminum sulfate, and aluminum lactate are preferably used.
[0052] The polyvalent cation is used in an amount of, for example, 0.001 to 1.5 wt %, preferably 0.005 to 1 wt %, particularly preferably 0.02 to 0.8 wt %, based on the polymer.
[0053] The surface postcrosslinking is carried out by spraying a solution of the surface postcrosslinker onto the dried superabsorbent particles. After spraying, the superabsorbent particles coated with the surface postcrosslinker are subjected to thermal surface postcrosslinking.
[0054] The solution of the surface postcrosslinker is preferably sprayed in a mixer with a moving stirring tool, such as a screw mixer, a pan mixer, or a paddle mixer. Horizontal mixers, such as paddle mixers, are particularly preferred, and vertical mixers are even more preferred. Horizontal mixers differ from vertical mixers in the way the stirring shaft is supported: horizontal mixers have a horizontally supported stirring shaft, while vertical mixers have a vertically supported stirring shaft. Suitable mixers are, for example, the Horizontal mixer. Mischer (Gebr. Maschinenbau GmbH; Paderborn; Germany), Vrieco-Nauta Continuous Mixer (Hosokawa Micron BV; Doetinchem; The Netherlands), Processall Mixmill Mixer (Processall Incorporated; Cincinnati; USA), and Schugi (Hosokawa Micron BV; Doetinchem; The Netherlands). However, it is also possible to spray on the surface postcrosslinker solution in a fluidized bed.
[0055] The surface postcrosslinkers are usually used as aqueous solutions. The penetration depth of the surface postcrosslinker into the superabsorbent particles can be adjusted via the content of non-aqueous solvent or the total amount of solvent.
[0056] The thermal surface postcrosslinking is carried out in a contact dryer, particularly preferably in a paddle dryer, and even more particularly preferably in a tray dryer. Suitable dryers are, for example, Hosokawa Horizontal PaddleDryer (Hosokawa Micron GmbH; Rheingarten; Germany), Hosokawa Disc Dryer (Hosokawa Micron GmbH; Rheingold
[0057] Teng; Germany), dryers (Metso Minerals Industries Inc.; Danville; USA) and Nara Paddle Dryer (NARA Machinery Europe; Frechen; Germany).
[0058] The surface postcrosslinked superabsorbent particles can subsequently be reclassified, with oversized and / or oversized superabsorbent particles being separated and fed back to the process.
[0059] To further improve the properties, the surface postcrosslinked superabsorbent particles can be coated or remoistened.
[0060] Remoistening is preferably carried out at 30°C to 80°C, particularly preferably at 35°C to 70°C, and even more preferably at 40°C to 60°C. At temperatures that are too low, the superabsorbent particles tend to agglomerate, while at higher temperatures, water evaporates significantly. The amount of water used for remoistening is preferably 1% to 10% by weight, particularly preferably 2% to 8% by weight, and even more particularly preferably 3% to 5% by weight. Remoistening enhances the mechanical stability of the superabsorbent particles and reduces their tendency to become electrostatically charged. Remoistening is preferably carried out in a cooler after hot surface postcrosslinking.
[0061] Suitable coatings for improving the swelling rate and the gel bed permeability (GBP) are, for example, inorganic inert substances (such as water-insoluble metal salts), organic polymers, cationic polymers and divalent or polyvalent metal cations. Suitable coatings for binding dust are, for example, polyols. Suitable coatings for counteracting the unfavorable tendency of superabsorbent particles to agglomerate are, for example, fumed silica (such as 200), precipitated silica (such as D17) and surfactants (such as 20).
[0062] Example 1 (according to the present invention)
[0063] A monomer solution was prepared by continuously mixing deionized water, 48 wt% sodium hydroxide solution and acrylic acid so that the degree of neutralization was equal to 72.0 mol%. The water content of the monomer solution was 57.0 wt%.
[0064] Triethoxylated glycerol triacrylate (approximately 85 wt%) was used as a crosslinker. The dosage was 0.99 kg per ton of monomer solution. Additionally, polyethylene glycol with an average molecular weight of 4000 g / mol was added to the monomer solution. The dosage was 2.64 kg per ton of monomer solution.
[0065] To initiate free radical polymerization, 0.99 kg of a 0.25 wt% aqueous hydrogen peroxide solution, 4.38 kg of a 15 wt% aqueous sodium peroxodisulfate solution, and 0.88 kg of a 1 wt% aqueous ascorbic acid solution were added per ton of monomer solution.
[0066] The monomer solution was added to a List Contikneter with a 6.3m 3 The reactor was a 1.5-liter reactor (LISTAG, Aristof, Switzerland). The throughput of the monomer solution was about 20 t / h. The temperature of the reaction solution at the inlet was 23.5°C.
[0067] The monomer solution was inerted with nitrogen between the crosslinker addition point and the hydrogen peroxide and sodium peroxodisulfate solution addition points. Ascorbic acid was added directly to the reactor. Additionally, a 20 wt% aqueous solution of 1-hydroxyethylidene-1,1′-diphosphonic acid disodium salt (etidronic acid) was added to the reactor. The solution dosage was 6.17 kg per ton of monomer solution.
[0068] After approximately 50% of the residence time, approximately 1,000 kg / h of superabsorbent particles with a particle size of less than 150 μm, resulting from comminution and classification during the production process, were additionally fed into the reactor. The residence time of the reaction mixture in the reactor was approximately 15 minutes.
[0069] The resulting polymer gel was conveyed via a vibrating conveyor belt to the conveyor belt of a circulating air belt dryer. The circulating air belt dryer was 48 m long. The conveyor belt of the circulating air belt dryer had an effective width of 4.4 m. The aqueous polymer gel was continuously circulated and dried in the circulating air belt dryer using an air / gas mixture (approximately 175° C.). The residence time in the circulating air belt dryer was 37 minutes.
[0070] The dried polymer gel is comminuted using a three-stage roller mill and sieved to a particle size of 150 to 710 μm. Superabsorbent particles with a particle size of less than 150 μm are separated. Superabsorbent particles with a particle size of greater than 710 μm are returned for comminution. The superabsorbent particles in the particle size range of 150 to 710 μm are subjected to thermal surface postcrosslinking.
[0071] In Schugi The superabsorbent particles were coated with a surface postcrosslinker solution in a NARA Micron (Hosokawa Micron BV, Doetinchem, The Netherlands) and subsequently thermally surface postcrosslinked in a NARA Paddle Dryer (Contact Dryer 1, GMF Gouda, Wadinksveen, The Netherlands) at 120° C. for 45 minutes.
[0072] Add the following amount of materials to Schugi
[0073] 7.5t / h super absorbent granules
[0074] 361.5kg / h surface post-crosslinker solution
[0075] The surface postcrosslinker solution contained 0.87 wt % of ethylene glycol dimethacrylate, 32.78 wt % of 1,2-propylene glycol, 1.10 wt % of aluminum sulfate, and 65.25 wt % of water.
[0076] The surface postcrosslinked superabsorbent particles were conveyed via an impeller rotary valve to a NARA Pad-dle Cooler (Contact Dryer 2, GMF Gouda, Waddington, The Netherlands) and cooled to approximately 60° C. The surface postcrosslinked superabsorbent particles were coated with 576.75 kg / h of an aqueous solution containing 0.65 wt % aluminum sulfate and 0.065 wt % sorbitan monolaurate. The aqueous solution is added through two opposing two-component nozzles below the product bed surface. The angle to the vertical is 48°. The two-component nozzles are approximately 1135 mm to 1280 mm from the end wall. The paddles have a diameter of approximately 0.9 m and rotate at approximately 10 revolutions per minute. The residence time is approximately 20 minutes.
[0077] The superabsorbent particles obtained contain only very few agglomerates.
[0078] Example 2 (not according to the invention)
[0079] The procedure was carried out as in Example 1. The aqueous solution was added only via the first two-component nozzle. The distance between the two-component nozzle and the end wall was approximately 1280 mm.
[0080] The superabsorbent particles obtained contain only a large number of agglomerates.
[0081] Example 3 (not according to the invention)
[0082] The operation was carried out as in Example 1. The aqueous solution was added via two consecutive two-component nozzles, the distance between the two-component nozzles and the end wall being approximately 1280 mm to 2295 mm.
[0083] The superabsorbent particles obtained contain only agglomerates.
Claims
1. A method for preparing a superabsorbent, wherein: The superabsorbent particles are coated by spraying a surface postcrosslinker solution, the coated superabsorbent particles are thermally surface postcrosslinked in a contact dryer 1, and the thermally surface postcrosslinked superabsorbent particles are cooled in a contact dryer 2, characterized in that the contact dryer 2 has two horizontal shafts with stirring tools, the rotational speed of the stirring tools corresponds to a Froude number of 0.005 to 0.25, and the granular solid matter, the aqueous solution and / or the dispersion are respectively added to the contact dryer 2 via at least one first nozzle in the first horizontal axis area and at least one second nozzle in the second horizontal axis area.
2. The method according to claim 1, characterized in that The rotation speed of the stirring tool corresponds to a Froude number of 0.05 to 0.
15.
3. The method according to claim 1 or 2, characterized in that The granular solid material, the aqueous solution and / or the dispersion are fed into the contact dryer 2 below the surface of the product bed.
4. The method according to any one of claims 1 to 3, characterized in that The residence time of the superabsorbent particles in the contact dryer 2 is 10 to 60 minutes.
5. The method according to any one of claims 1 to 4, characterized in that The particulate solid material, aqueous solution and / or dispersion is added in an amount of 0.001 to 2.0 wt %, based on the superabsorbent particles.
6. The method according to any one of claims 1 to 5, characterized in that The stirring tool has a diameter of 0.2 m to 2 m.
7. The method according to any one of claims 1 to 6, characterized in that The rotation speed of the stirring tool is less than 25 revolutions per minute.
8. The method according to any one of claims 1 to 7, characterized in that Silicon dioxide, aluminum oxide and / or aluminum trihydroxide are used as the particulate solid material.
9. The method according to any one of claims 1 to 8, characterized in that An aqueous solution of polyethylene glycol, an aluminum salt and / or a surfactant is used as the aqueous solution.
10. The method according to any one of claims 1 to 9, characterized in that The superabsorbent particles are cooled in the contact dryer 2 to a temperature of 30 to 80°C.
11. The method according to any one of claims 1 to 10, characterized in that Partially neutralized, cross-linked polyacrylic acid is used as superabsorbent.
12. The method according to any one of claims 1 to 11, characterized in that The surface postcrosslinker is a compound that is able to form covalent bonds with the superabsorbent.
13. The method according to any one of claims 1 to 12, characterized in that The temperature of the superabsorbent particles during the spraying of the surface postcrosslinker solution is from 30°C to 80°C.
14. The method according to any one of claims 1 to 13, characterized in that The superabsorbent particles are heated in the contact dryer 1 to a temperature of 110°C to 220°C.
15. The method according to any one of claims 1 to 14, characterized in that The residence time of the superabsorbent particles in the contact dryer 1 is 10 to 60 minutes.
Citation Information
Patent Citations
Process for post-crosslinking of a water absorbing polymer surface with a cyclic urea useful in foams, fibers, films, cables, especially sealing materials, liquid absorbing hygiene articles, packaging materials, and soil additives
DE10204938A1
(Meth)acrylic acid esters of monoalkoxylated polyols and their preparation
DE10331450A1
(Meth)acrylic acid esters of alkoxylated unsaturated polyol ethers and their preparation
DE10331456A1
(Meth)acrylic acid esters of unsaturated amino alcohols and their preparation
DE10355401A1
Water-absorbing polymers with improved properties, processes for their production and their use
DE19543368A1